Robust 3D registration and tracking with RGBD sensors - Amamra, A (Cranfield University, 2015)
This thesis investigates the utilisation of cheap RGBD sensors in rigid body tracking and 3D multiview registration for augmented and Virtual reality applications. RGBD sensors can be used as an affordable substitute for the more sophisticated, but expensive, conventional laser-based scanning and tracking solutions. Nevertheless, the low-cost sensing technology behind them has several drawbacks such as the limited range, significant noisiness and instability. To deal with these issues, an innovative adaptation of Kalman filtering scheme is first proposed to improve the precision, smoothness and robustness of raw RGBD outputs. It also extends the native capabilities of the sensor to capture further targets. The mathematical foundations of such an adaptation are explained in detail, and its corrective effect is validated with real tracking as well as 3D reconstruction experiments. A Graphics Processing Unit (GPU) implementation is also proposed with the different optimisation levels in order to ensure real-time responsiveness. After extensive experimentation with RGBD cameras, a significant difference in accuracy was noticed between the newer and ageing sensors. This decay could not be restored with conventional calibration. Thus, a novel method for worn RGBD sensors correction is also proposed. Another algorithm for background/foreground segmentation of RGBD images is contributed. The latter proceeds through background subtraction from colour and depth images separately, the resulting foreground regions are then fused for a more robust detection. The three previous contributions are used in a novel approach for multiview vehicle tracking for mixed reality needs. The determination of the position regarding the vehicle is achieved in two stages: the former is a sensor-wise robust filtering algorithm that is able to handle the uncertainties in the system and measurement models resulting in multiple position estimates; the latter algorithm aims at merging the independent estimates by using a set of optimal weighting coefficients. The outcome of fusion is used to determine vehicle’s orientation in the scene. Finally, a novel recursive filtering approach for sparse registration is proposed. Unlike ordinary state of the art alignment algorithms, the proposed method has four advantages that are not available altogether in any previous solution. It is able to deal with inherent noise contaminating sensory data; it is robust to uncertainties related to feature localisation; it combines the advantages of both L2 , L (infinity) norms for a higher performance and prevention of local minima; it also provides an estimated rigid body transformation along with its error covariance. This 3D registration scheme is validated in various challenging scenarios with both synthetic and real RGBD data.
Keywords: Kalman filtering; RGBD camaera